Assessment of different methods of determining confidence intervals for the difference of binomial proportions - Nel, Mariette (University of the Free State, 1998)
Abstract not available
Keywords: Confidence intervals; Analysis of variance; Dissertation (M.Med.Sc. (Biostatistics))--University of the Free State, 1998